Examination of Structural and Electrical Properties of CuO-Doped CdO Nanocomposites Produced by the Hydrothermal Method - Yildiz, Tulay; Kati, Nida; Gul, Busra (Wiley-V C H Verlag Gmbh, 2022)
In this study, pure CdO and CdO-CuO nanopowders with different dopant concentrations are synthesized by the hydrothermal method. Structural properties of the nanopowders are characterized by X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR), morphological properties and elemental analyses are characterized by Field Emission Scanning Electron Microscopy (FESEM), optical properties are characterized by UV-vis spectroscopy, and electrical properties are characterized by the current-voltage technique. XRD data show that nanopowders are polycrystalline and crystallinity decreases with the doping concentration. In the analysis of FESEM images, it can be concluded that the morphology of the particles is shaped as needle-like, spherical-like, and randomly oriented nanorods forms from the cube form. Also, by joining those nanorods, spherical-like microstructures occur, and while the dopant concentration increases, echinus-like forms are obtained. The energy bandgap of the nanopowders decreases with an increased dopant concentration of CuO. It is observed that the dopant concentration of CuO also changes the electrical properties.
Keywords: CdO; CuO; electrical conductivity; hydrothermal method; nanopowders